IIUM Special Plate number - Mohamed Osman, Mariana; Shuid, Syafiee; Rabe, Noor Suzilawati; Muhamad Yusop, Siti Wahidah; Che Mohd Hashim, Ahmad Kamil; Hasbullah, Hafizah (2021)
A well-designed brochure serves as a perfect introduction to the IIUM Special Plate event. A brochure for IIUM Special Plate Number is to describe the products and services given. This brochure designed according to the latest innovative way and act as reference material to the public